Utilization of Resource Maritime Museum of Jakarta as an Attractive Cultural Tourism Destination - ., Priyanto (KnE Social Sciences, 2018)
This study aims to examine the Utilization of Resources Museum Bahari Jakarta as a Culture Tourism Attraction. This research uses qualitative research approach method with descriptive analysis. Stages in this research are observation, description and interpretation through cultural tourism and museology concepts. The research is expected to yield optimal results on how to make the Resources Museum Bahari Jakarta a cultural tourism attraction. The results of this study are also expected to be able to present the role and function of the Maritime Museum of Jakarta through various presentations that can be useful for the community. Keywords: cultural tourism, Maritime Museum Jakarta